2008
DOI: 10.1901/jaba.2008.41-117
|View full text |Cite
|
Sign up to set email alerts
|

Peer Tutoring to Prevent Firearm Play: Acquisition, Generalization, and Long‐term Maintenance of Safety Skills

Abstract: Hundreds of accidental injuries and deaths to children occur annually in the United States as a result of firearm play. Behavioral skills training (BST) and in situ training have been found to be effective in teaching children the skills to use if they find a firearm, but training requires substantial time and effort. The current study examined the use of peers as tutors as a potential way to decrease the time and resources needed to teach these safety skills to youngsters. Peer trainers conducted BST and in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 12 publications
1
24
0
1
Order By: Relevance
“…The peer trainers also demonstrated the safety skills during in-situ assessments following training. These findings are similar to the results of Jostad et al (2008) who demonstrated the effectiveness of peer training for teaching firearm injury prevention skills. During baseline assessments, the trainers and students did not engage in all of the safety skills when presented with abduction lures from strangers.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The peer trainers also demonstrated the safety skills during in-situ assessments following training. These findings are similar to the results of Jostad et al (2008) who demonstrated the effectiveness of peer training for teaching firearm injury prevention skills. During baseline assessments, the trainers and students did not engage in all of the safety skills when presented with abduction lures from strangers.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, in a recent study by Jostad, Miltenberger, Kelso, and Knudson (2008), older peer trainers used BST and IST successfully to teach younger children the skills necessary to avoid playing with firearms to prevent unintentional firearm injury. Considering the success of peer training in general and with safety skills in particular in the Jostad et al (2008) study, the purpose of the present study is to evaluate the effectiveness of peer trainers in teaching abduction prevention skills.…”
mentioning
confidence: 99%
“…Embedding: systemic approaches At this point let us consider a completely different kind of study -that by Jostad, Miltenberger, Kelso, and Knudson (2008). They noted that hundreds of accidental injuries and deaths to children occurred annually in the United States as a result of firearm play.…”
Section: Information Technology and Peer Learningmentioning
confidence: 99%
“…Using BST and IST, the older children successfully taught the younger children the skills. This study showed that the peers were able to implement the training and that both the peer conducting training and the child receiving training demonstrated the correct skills in an in situ assessment (Jostad & Miltenberger, 2004;Jostad et al, 2008).…”
Section: Introductionmentioning
confidence: 77%
“…Training by parents in the home can help contribute to the generalization of the skills and could potentially reach more children. In another study peers were trained to implement behavioral skills training to other students (Jostad, Miltenberger, Kelso, & Knudson, 2008). Older children, ages 6 and 7, were asked to teach younger children, ages 4 and 5.…”
Section: Introductionmentioning
confidence: 99%